Kesalahan Ustaz dalam Bahasa Arab Verbal pada Penyampaian Materi Dakwah Islam - Mushodiq, Muhamad Agus; Syaifullah, Muhammad; Amalia, Dian Risky; Izzah, Nailul; Pratiwi, Bety Dwi (Arabiyatuna: Jurnal Bahasa Arab, 2021)
This paper aims to reveal the mistakes of micro Arabic in the aspects of Ilm Saut (phonology), Sharaf (morphology), Nahw (Syntax), and 'Ilm Dalalah (Semantics) in preaching materials conveyed by ustadz and ustadzah included in the groups of "Ustadz Sunnah" and "Islam itu Indah". Arabic mistakes are often made by ustadz and ustadzah who often appear on social media. In general, an ustadz must have good Arabic language skills. The vast emergence of ustadz and ustadzah on social media is allegedly not accompanied by their qualified mastery of the primary language used in Islamic teaching sources and primary books, namely Arabic. Hence, the researchers used micro linguistic theories comprising the studies of phonology, morphology, syntax, and semantics therein. This study applied a descriptive-qualitative method. Researchers not only described the Arabic mistakes made by those of "Ustadz Sunnahâ€ and "Islam itu Indah" but also provided corrections to such mistakes. In analyzing the data, the researchers used a separate analysis method. The findings demonstrated that those of "Ustaz Sunnah" and "Islam itu Indahâ€ made mistakes in verbal Arabic at phonemic, morphemic, syntactic, and semantic levels.